Music and the City: Musical Cultures and Urban Societies in the Southern Netherlands and Beyond, c. 1650-1800 - Beghein, Stefanie; Blondé, Bruno 1964-; Schreurs, Eugeen; Forment, Bruno 1978- (Leuven Leuven University Press, 2013)
The societal dimension of music in urban life in the late seventeenth and eighteenth centuries. Although early modern urban musical life has been the object of investigation with several researchers, little is known about the ways in which musical cultures were integrated within their broader urban environments. Building upon recent trends within urban musicology, the authors of this volume aim to transcend descriptive overviews of institutions and actors involved with music within a given city. Instead, they consider the urban environment as the constitutive context for music making, and music as a significant aspect of urban society and identity. Through selected case studies and by focusing on three 'musical circuits'-opera and theatre music, sacred music, and secular songs-this book contributes to a more effective understanding of music in late seventeenth- and eighteenth-century urban societies in the southern Netherlands and beyond.
Includes bibliographical references.
Keywords: 17th Century (1601-1700); 18th Century (1701-1800); Music history; Europe; Flanders (Belgium)